Migraine with aura and TCD bubble-test: The significance of positive result - Podgorac, Ana; Zidverc-Trajković, Jasna; Jovanović, Zagorka; Radojičić, Aleksandra; Pavlović, Aleksandra; Mijajlović, Milija; Švabić-Medjedović, Tamara; Čovičković-Šternić, Nadežda (Vojnosanitetski pregled, 2015)
Background/Aim. The association between the right-to left shunt (RLS) and migraine with aura (MA) has been proven so far. The aim of this study was to determine if the presence of RLS detected as a result of transcranial doppler (TCD) bubble-test, makes any difference in clinical presentation, aura and headache in patients with MA. Methods. A single-group descriptive study was conducted on 153 patients diagnosed with MA. TCD bubble-test was performed on 135 of them. The recorded demographic and clinical features of patients were analyzed and compared with the results of the TCD bubble test. Results. In the group of 135 patients, 88 (65.2%) had positive TCD bubble-test. The difference in the investigated clinical features of patients of the patients and aura between the patients with and without RLS, was not found. Conclusion. The results of our study confirm a high prevalence of right-to-left shunt in patients with MA, but the clinical relevance of this association was not shown.